2020
DOI: 10.5965/223811711932020377
|View full text |Cite
|
Sign up to set email alerts
|

First report: Amazon River Prawn reared in biofloc technology

Abstract: The objective of this work was to evaluate the use of biofloc technology to reared Amazon River prawn (Macrobrachium amazonicum). One hundred Amazon River prawn juveniles were divided into two experimental units (250 L), 50 animals per each. Prawns were fed two times per day, with 3% of the prawn biomass.  Dissolved oxygen and temperature were performed twice a day. Total suspended solids, pH, alkalinity, ammonia nitrogen, nitrite and nitrate were monitored twice a week. Prawns showed 77.67%, survival, 2.98 fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The specific growth rate (SGR) was identified ranged between 6.02 to 6.98 %/day which highest SGR identified from maize starch treatment (Hosain et al, 2021). It is highly potential to apply biofloc in culturing of Amazon river prawn, Macrobrachium amazonicum, but the actual nutritional diet and management techniques have to be improved for this species to make it more successful to be cultured with biofloc technology (Jatoba et al, 2020) Research conducted on the monoculture, polyculture and Recirculation Aquaculture System (RAS) using mixed culture of tilapia and giant freshwater prawn in biofloc system found out that both monoculture and polyculture system improved the prawn's growth and survival rate using biofloc application (Hisano et al, 2020). The prawn achieved weight gains of 65.4% compared to the prawn cultured in the RAS system from the biofloc consumption as additional feed and it was suggested that polyculture of Nile tilapia, O. niloticus with Giant freshwater prawn, M. rosenbergii with biofloc can be promoted as an eco-friendly aquaculture model for the production (Hisano et al, 2020).…”
Section: Biofloc Applications In Freshwater Prawn Aquaculturementioning
confidence: 99%
“…The specific growth rate (SGR) was identified ranged between 6.02 to 6.98 %/day which highest SGR identified from maize starch treatment (Hosain et al, 2021). It is highly potential to apply biofloc in culturing of Amazon river prawn, Macrobrachium amazonicum, but the actual nutritional diet and management techniques have to be improved for this species to make it more successful to be cultured with biofloc technology (Jatoba et al, 2020) Research conducted on the monoculture, polyculture and Recirculation Aquaculture System (RAS) using mixed culture of tilapia and giant freshwater prawn in biofloc system found out that both monoculture and polyculture system improved the prawn's growth and survival rate using biofloc application (Hisano et al, 2020). The prawn achieved weight gains of 65.4% compared to the prawn cultured in the RAS system from the biofloc consumption as additional feed and it was suggested that polyculture of Nile tilapia, O. niloticus with Giant freshwater prawn, M. rosenbergii with biofloc can be promoted as an eco-friendly aquaculture model for the production (Hisano et al, 2020).…”
Section: Biofloc Applications In Freshwater Prawn Aquaculturementioning
confidence: 99%